The Effect of Debt To Equity Ratio, Total Asset Turnover, Return On Assets And Return On Equity On Dividend Policy In Manufacturing Companies - PURWANTO, Indrawan; SANJAYA, I Ketut Puja Wirya; KAWISANA, Putu Gede Wisnu Permana (PT Keberlanjutan Strategis Indonesia, 2021)
An industry has a clear goal, which is to reap profits in each of its performances, the profits generated by the industry in its performance cannot be separated from the donations of financial managers. The purpose of this study is to find out that dividend policy can increase business growth and development. The study method uses secondary data, obtained from the annual report of each industry with the year published 2015, 2016, 2017, 2018 and 2019. The total population of 182 obtained by 25 industries as an illustration with a year of observation as far as 5 years, so that an illustration of as many as 182 is obtained. 125 observations. The conclusions obtained in the results of this study that investors and potential corporate investors will be more careful and also pay attention to financial ratios that can be considered in carrying out investments.